A bibliometric and classification study of Project-based Learning in engineering education - Reis, Ana Carla Bittencourt (2017)
Engineering education has been the subject of studies in search of approaches that provide better results in terms of learning. The Project Based Learning approach (PBL) is the subject of this study from the point of view of its application in Engineering. The objective is to present a classification and bibliometric analysis of PBL in Engineering. Publications on the subject were identified through queries at the journal databases at ISI Web of Science and Scopus SCImago between 2000 and 2016. The results highlight the benefits from the use of the PBL approach to learning in Engineering showing increased absorption of technical content by students and the development of soft and multi-disciplinary skills. The bibliometric analysis revealed the most relevant journals in the subject, authors and the most cited papers and keywords. New horizons to advance the use of PBL in engineering education are discussed.